Control of free electron wave packets by polarization-tailored ultrashort bichromatic laser fields. Issue 1 (1st January 2019) - Kerbstadt, S.; Eickhoff, K.; Bayer, T.; Wollenhaupt, M.
ABSTRACT: We review recent advances in the generation of polarization-tailored ultrashort bichromatic laser fields and their application to the coherent control of ultrafast photoionization dynamics. In the experiments, we use polarization-shaped bichromatic laser pulses to control three-dimensional photoelectron momentum distributions from atomic multiphoton ionization. To analyze the underlying physical mechanisms, we consider two bichromatic control schemes based on high-order intrapulse frequency mixing and interband N 1 - vs. N 2 -photon interference, respectively. In the first scheme, interferometric ( ω :2 ω ) fields are used to select or suppress specific ionization channels in the resonance-enhanced 2-photon ionization of potassium atoms by second-order intrapulse frequency mixing. In the second scheme, we utilize a white light polarization pulse shaper to generate carrier-envelope phase-stable (3 ω :4 ω ) fields in order to manipulate the symmetry properties of photoelectron wave packets from 3- vs. 4-photon ionization of sodium atoms. In both cases, bichromatic polarization control of free electron wave packets is based on the creation of a superposition of multiple angular momentum states with different kinetic energy spectra. We discuss the vorticity of these mixed angular momentum states and show that the kinetic energy spectra are determined by the bichromatic multiphoton spectra, emphasizing the close relationship between bichromatic multiphoton ionization and nonlinear optical spectroscopy. Graphical abstract: